Level of contact hypersensitivity response to diphencyprone and keratinocyte cancer. (19th July 2019) - Bullen, A.; Polcz, M.; Rowe, C.J.; Byrom, L.; Soyer, H.P.; Khosrotehrani, K.
Abstract: Background: Keratinocyte cancers (KC) are common and pose a significant financial burden globally. Ultraviolet radiation is a significant factor in their development, through mutagenesis promotion but also through local and systemic immunosuppression. Although systemic immunosuppression is well understood, cutaneous immunity has been more difficult to evaluate. Objectives: This study used a contact sensitizer, diphencyprone (DPCP), which elicits a contact hypersensitivity reaction in skin, to compare the degree of reactivity to DPCP in patients with a high KC burden versus those with a low KC burden. Methods: A prospective study was performed in immunocompetent patients aged 70 ± 5 years of age, comparing patients with a high KC burden (>10 previous KC) with those with a low KC burden (<2 previous KC). All patients were sensitized with 2% DPCP and then patch tested two weeks later with eight different concentrations of DPCP with the threshold concentration and total degree of reaction recorded. Results: Nine patients were recruited, 5 in the 'high cancer' group and 4 in the 'low cancer' group. All patients were Fitzpatrick skin type 1 or 2. All patients developed a reaction to DPCP. Patients in the low cancer group developed a reaction at a significantly lower threshold DPCP concentration than the high cancer group ( P  = 0.039). The cumulative intensity of reaction was higher in the low cancer group ( P  = 0.087). Conclusion: Patients with a high KC burden required a higher threshold concentration of DPCP to elicit a hypersensitivity reaction, supporting the concept of a lower skin immunity in these patients. DPCP reactivity threshold could be a useful tool in the evaluation of skin immunity and propensity to develop keratinocyte cancers. Abstract : Linked Commentary: R. Happle. J Eur Acad Dermatol Venereol 2019; 33 : 2012–2013. https://doi.org/10.1111/jdv.15942 .